Competition in Persuasion - Gentzkow, Matthew; Kamenica, Emir (Review of Economic Studies, 2017)
We study symmetric information games where a number of senders choose what information to communicate. We show that the impact of competition on information revelation is ambiguous in general. We identify a condition on the information environment (i.e., the set of signals available to each sender) that is necessary and sufficient for equilibrium outcomes to be no less informative than the collusive outcome, regardless of preferences. The same condition also provides an easy way to characterize the equilibrium set and governs whether introducing additional senders or decreasing the alignment of senders' preferences necessarily increases the amount of information revealed.